ANALYSIS OF THE WEAKNESSES OF HYBRID LEARNING DURING THE PANDEMIC: CASE STUDY IN BASIC NATURAL SCIENCE (BNS) LECTURES - Syazali, Muhammad; ERFAN, MUHAMMAD; WAHDAH, NOVA FITRIANI (JURNAL EDUSCIENCE, 2023)
Data on deficiencies regarding preparation, planning, processes and assessment is the information needed to make improvement efforts in the future. Therefore, this research was conducted to analyze the weaknesses of hybrid learning implemented in Basic Natural science (BNS) courses. This qualitative descriptive research was carried out at the Primary Teacher Education (PTE) Study Program during the preparation, planning, learning and assessment of learning outcomes. Qualitative data was collected using observation and documentation methods. The collected data was analyzed using qualitative analysis from Miles and Huberman. The weaknesses of hybrid learning that we found include coordination carried out with senior lecturers whose expertise is non-science education, late submission of SIMAKSI to BKSDA, CPMK is limited to Science Process Skills (SPS), objectives only cover basic SPS, there are no guidelines for preparing reports, science topics are limited to ecosystems, multi tasking, the learning time interval is only two weeks, the SPS instrument only uses tests, and the tests are carried out online. It is hoped that these results can be used as evaluation material in order to improve the implementation of hybrid learning in science courses, especially BNS.Keywords: Basic natural sciences, weaknesses, hybrid learning.AbstrakData kekurangan tentang persiapan, perencanaan, proses dan assessment merupakan informasi yang dibutuhkan untuk melakukan upaya perbaikan dimasa yang akan datang. Oleh karena itu, penelitian ini dilakukan untuk menganalisis kelemahan pembelajaran hybrid yang diimplementasikan pada mata kuliah IKD. Penelitian deskriptif kualitatif ini dilaksanakan pada Prodi PGSD selama proses persiapan, perencanaan, pembelajaran sampai dengan penilaian hasil belajar. Data kualitatif dikumpulkan menggunakan metode observasi dan dokumentasi. Data yang terkumpul dianalisis menggunakan analsisi kualitatif dari Miles and Huberman. Kelemahan pembelajaran hybrid yang kami temukan di antaranya koordinasi dilakukan dengan dosen senior yang keilmuannya non-pendidikan sains, telatnya pengajuan SIMAKSI ke BKSDA, CPMK terbatas pada KPS, tujuan hanya mencakup KPS dasar, tidak ada pedoman penyusunan laporan, topik sains dibatasi pada ekosistem, multi tasking, interval waktu pembelajaran hanya dua minggu, instrumen KPS hanya menggunakan tes, dan pelaksanaan tes dilaksanakan secara daring. Hasil ini diharapkan dapat menjadi bahan evaluasi dalam rangka memperbaiki implementasi hybrid learning pada mata kuliah sains khususnya IKD.Kata Kunci: ilmu kealamiahan dasar, kelemahan, pembelajaran hybrid